Current Challenges of Dramatic Writing in Burkina Faso : Institutional and Aesthetic Perspectives - (:unkn) unknown (My University, 2022)
Beginning with the observation of the marginalized place of dramatic texts, or plays, in Burkina Faso, I propose to shine light on the legitimacy, circulation, and dissemination of the plays starting from the city of Ouagadougou, which is considered a cultural centre. When opportunities for publication are insufficient, writers produce plays at the intersection of producing networks, (urban, pan-African, Francophone), and thus have the possibility for their work to exist separately from conventional forms of legitimization. The implementation of a pluralistic method: the identification of published plays, the collection of unpublished plays, or extracts from plays written in Mooré translated into French allows me to deconstruct the mechanizations of critical marginalization and to read together dramatic texts of different statures.The analysis of these texts in light of the contexts of their institutional production reveals the cosmopolitan dynamics of African literature from a different point of view, that of an African literary space. The texts appear as a place for constituting an understanding equally of literature and of theatre. Finally, this work explores the possibility of the dramatic texts to reinforce, question, and negotiate the general sharing through the institutional and scenic criteria.
Keywords: African Research